2010
DOI: 10.1371/journal.ppat.1001167
|View full text |Cite
|
Sign up to set email alerts
|

Nucleocapsid Promotes Localization of HIV-1 Gag to Uropods That Participate in Virological Synapses between T Cells

Abstract: T cells adopt a polarized morphology in lymphoid organs, where cell-to-cell transmission of HIV-1 is likely frequent. However, despite the importance of understanding virus spread in vivo, little is known about the HIV-1 life cycle, particularly its late phase, in polarized T cells. Polarized T cells form two ends, the leading edge at the front and a protrusion called a uropod at the rear. Using multiple uropod markers, we observed that HIV-1 Gag localizes to the uropod in polarized T cells. Infected T cells f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

9
117
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(127 citation statements)
references
References 168 publications
(225 reference statements)
9
117
1
Order By: Relevance
“…The hypothesized dual function of the C-tail of Env in the modulation of adhesive interfaces and the recruitment of MA would explain why the determinants identified here are distinct from the requirements for Env incorporation into virions (28; Marc Johnson, unpublished data). It is also worth mentioning that the adhesion-induced polarity described here is distinct from the polarity observed in primary migrating T cells, in which HIV Gag is polarized to the uropod by an Env-independent mechanism (24).…”
Section: Discussionmentioning
confidence: 54%
“…The hypothesized dual function of the C-tail of Env in the modulation of adhesive interfaces and the recruitment of MA would explain why the determinants identified here are distinct from the requirements for Env incorporation into virions (28; Marc Johnson, unpublished data). It is also worth mentioning that the adhesion-induced polarity described here is distinct from the polarity observed in primary migrating T cells, in which HIV Gag is polarized to the uropod by an Env-independent mechanism (24).…”
Section: Discussionmentioning
confidence: 54%
“…187 At the same time, the nucleocapsid protein of HIV-1 promotes localization of virus structural proteins to uropods of polarized T cells, which may contribute to virus transfer via T-cell-T-cell contacts through so-called virological synapses, a process that depends on cytoskeletal remodeling. 189,190 Nef-PAK2 also affects T lymphocyte migration, as it leads to inactivation of cofilin, a downstream effector of PAK signaling, which results in reduced chemoattractant-induced T cell motility. 168,176 Importantly, the Nef-PAK2 interaction also interferes with T-lymphocyte circulation in vivo.…”
Section: Interactions With the Immune Systemmentioning
confidence: 99%
“…Indeed, previous studies suggested that most membrane proteins are incorporated into retrovirus particles passively, i.e., with no enrichment relative to the plasma membrane (28). During assembly, Gag has been observed to associate with plasma membrane microdomains, such as lipid rafts (29,30) and tetraspanin-enriched microdomains (TEMs) (31)(32)(33)(34)(35)(36), and reorganize these domains in ways that do not occur in uninfected cells (37)(38)(39). Therefore, at least a subset of membrane proteins (e.g., glycosylphosphatidylinositol-anchored proteins and tetraspanins) may be incorporated into virions actively (as opposed to by passive incorporation, which does not involve enrichment of membrane proteins at assembly sites) without specific interactions, other than association with the plasma membrane microdomains.…”
mentioning
confidence: 99%